Knowledge, Attitude and Prevention Practice Among the Volunteers (HCPS) in Implementing 5M - Julia Christy Labetubun; Dian Ayubi; Tri Krianto (Journal Research of Social Science, Economics, and Management, 2022)
Health care providers (HCP) are a group that has a high risk of being exposed to COVID-19. Due to the large number of personnel needed to handle COVID-19, in several hospitals, health volunteers were involved to assist in the treatment process. As workers who deal directly with COVID-19 patients, volunteers are the targets in this study. HCP's health behavior can influence the escalation of prevention and control cases at their level. Therefore, this study aims to examine the practice of knowledge, attitudes, prevention (KAP) and factors related to the application of 5M on volunteers (HCP) at Hospital "X", Jakarta, Indonesia. This type of research is a quantitative study, with a cross-sectional research design. A cross-sectional study, with multiple logistic regression analysis conducted on 232 volunteers (HCP) in 2021. The instrument used was a modified questionnaire from 7 previous studies, both regional and international, which have been tested for validity and reliability in the same study. group (30 volunteers) and the same hospital. Based on the results, it was found that the implementation of 5M volunteers were categorized as "poor prevention practices" (67.7%), "inadequate knowledge" (58.2%) and "negative attitudes" (55.2%), with R square through multivariate test of 0.630 which means that the influence of the independent variable on the dependent variable is 63% and the variables related to 5M behavior (p-value <0.05) are knowledge and attitudes. Attitude is known as the most dominant variable with a p-value of 0.014.